PENGARUH CYBERBULLYING BODY SHAMING TERHADAP MENTAL REMAJA - Helin Hel Lin (Media Keperawatan:Politeknik Kesehatan Makassar, 2021)
Cyberbullying Body Shaming is a form of bullying or bullying behavior through cyberspace communication technology that is used by someone to insult and harass others, where the victim cannot defend himself easily. Objective: to find out the relationship between cyberbullying body shaming and adolescent mentality. Methods: The sources of the articles used were obtained from searches through the Science Direct database, Google Cindekia and Google Scholar. Article search is restricted from 2016-2021. After the is obtained, then the article is reviewed until the stage of making a literature review. The keywords used in the article search were Body-Shaming, Cyberbullying, Teen Mental is literature review uses 15 articles that meet the inclusion criteria. Results: The relationship between Cyberbullying Body-Shaming from the research reviewed is strongly related to adolescent mental health, especially depression. Conclusion: Based on the results of a review of 15 journals on the Relationship of Cyberbullying Body-Shaming to Mental Adolescents, there is a relationship that Cyberbullying or body-shaming bullying is very influential on adolescent mentality, namely depression. Other influences also occur in teenager self-esteem, adolescent self-image, and social interaction in adolescents. There is even social anxiety and social withdrawal in adolescents who experience Cyberbullying Body shaming.